1989
DOI: 10.1144/sjg25010069
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon ages for a glaciomarine bed associated with the maximum of the Loch Lomond Readvance in west Benderloch, Argyll

Abstract: Synopsis Radiocarbon ages on shells of the high arctic marine mollusc Portlandia arctica collected from a glaciomarine bed immediately within the terminal position of the former Loch Lomond Readvance Creran glacier and probably overridden by it suggest that its maximum extent was reached during the second half (10 500–10 000 B.P.) of the Loch Lomond stade period and possibly as late as 10 000 B.P. Arctic marine faunas which flourished in the vicinity of this tidew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 18 publications
5
26
0
Order By: Relevance
“…These morphostratigraphic relationships have been observed elsewhere in the Scottish Highlands (e.g. Sissons, 1974) and have been suggested to indicate a two-phased Younger Dryas advance (see also Peacock et al, 1989;Merritt et al, 2003), whereby the outlet glaciers are suggested to have only briefly remained at their maximum positions, prior to slight retreat and stabilisation for longer further upvalley. Such a hypothesis of two-phase Younger Dryas glaciation may be tested in future as higher-resolution numerical dating methods are refined or become available.…”
Section: Timing Of Maximum Glaciationsupporting
confidence: 62%
“…These morphostratigraphic relationships have been observed elsewhere in the Scottish Highlands (e.g. Sissons, 1974) and have been suggested to indicate a two-phased Younger Dryas advance (see also Peacock et al, 1989;Merritt et al, 2003), whereby the outlet glaciers are suggested to have only briefly remained at their maximum positions, prior to slight retreat and stabilisation for longer further upvalley. Such a hypothesis of two-phase Younger Dryas glaciation may be tested in future as higher-resolution numerical dating methods are refined or become available.…”
Section: Timing Of Maximum Glaciationsupporting
confidence: 62%
“…At only a few sites has radiocarbon dating of the readvance proved feasible (e.g. Rose et al, 1988;Peacock et al, 1989). Comparison of the lithostratigraphy, pollen stratigraphy and/ or tephrostratigraphy of kettle hole and lake sites inside and outside the glacier limits has proved decisive in determining an LLS age for the readvance at some sites (e.g.…”
Section: The Loch Lomond Readvancementioning
confidence: 99%
“…Although the Loch Lomond Stade was terminated by rapid climate warming at ca. 11.5 cal kyr BP (Atkinson et al, 1987;Alley et al, 1993), there is evidence that glacier tongues had begun to retreat several centuries before the stadial termination, probably due to a reduction in snowfall (Rose et al, 1988;Peacock et al, 1989;Benn et al, 1992;Ballantyne and Harris, 1994). The final retreat of glacier ice in the upper Edendon Valley therefore may have occurred well before the end of the stade.…”
Section: Synthesis: Landscape Change In the Upper Edendon Valleymentioning
confidence: 99%